2010
DOI: 10.1121/1.3478782
|View full text |Cite
|
Sign up to set email alerts
|

Imprecise singing is widespread

Abstract: There has been a recent surge of research on the topic of poor-pitch singing. However, this research has not addressed an important distinction in measurement: that between accuracy and precision. With respect to singing, accuracy refers to the average difference between sung and target pitches. Precision, by contrast, refers to the consistency of repeated attempts to produce a pitch. A group of 45 non-musician participants was asked to vocally imitate unfamiliar 5-note melodies, as well as to sing a series of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
148
7
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(169 citation statements)
references
References 18 publications
13
148
7
1
Order By: Relevance
“…This criterion was based on categorizations of poor-pitch singers reported elsewhere (cf. Dalla Bella, Giguere, & Peretz, 2007;Pfordresher & Brown, 2007;Pfordresher, Brown, Meier, Belyk, & Liotti, 2010). The experimenter coded each trial as in tune if the majority of sampled f0 values were within these boundaries and out of tune if not.…”
Section: Vocal Imitationmentioning
confidence: 99%
“…This criterion was based on categorizations of poor-pitch singers reported elsewhere (cf. Dalla Bella, Giguere, & Peretz, 2007;Pfordresher & Brown, 2007;Pfordresher, Brown, Meier, Belyk, & Liotti, 2010). The experimenter coded each trial as in tune if the majority of sampled f0 values were within these boundaries and out of tune if not.…”
Section: Vocal Imitationmentioning
confidence: 99%
“…Performance on pitch matching and song singing has been found to be moderately correlated in a sample of kindergarteners (Demorest & Nichols, 2012) and highly correlated in a sample of adults (Pfordresher et al, 2010). Pfordresher and Brown (2007) suggested that single pitch, interval, and pattern tasks vary in terms of complexity because of the number of unique pitches they contain and varied in memory demand because of the total number of notes that they contain.…”
mentioning
confidence: 99%
“…Play songs and folk songs have been the test stimuli for many children's studies (Apfelstadt, 1984;Brophy, 1997;Flowers & Dunn-Sousa, 1990;Gault, 2002;Goetze, 1985;Green, 1994;Guerrini, 2006;Guilbault, 2004;Joyner, 1969;Muse, 1993;Roberts & Davies, 1975;Smith, 1973;Welch et al, 1997;Western, 2002;Wurgler, 1990;Young, 1971). Studies of singing in adults have used similar songs, such as Twinkle, Twinkle Little Star (Pfordresher, Brown, Meier, Belyk, & Liotti, 2010), Row-Row-Row Your Boat (McCoy, 1997Pfordresher et al, 2010), Jingle Bells Pfordresher et al, 2010), Brother John , Gens du Pays, Quebecois birthday song (Dalla Bella, Giguère, & Peretz, 2007), Happy Birthday (Pfordresher et al, 2010 ), a Polish happy birthday song , America (Phillips & Vispoel, 1990;Watts, Moore, & McCaghren, 2005), and O Music (Phillips & Vispoel, 1990).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Melodic accuracy and precision were measured for a group of 20 subjects using a methodology developed for singing assessment [46]. The task of the subjects was to sing ascending and descending intervals and short melodies as well as possible.…”
Section: Evaluation Of Melodic Accuracy and Precisionmentioning
confidence: 99%